Analysis and Design of Payment Reconciliation System on Airlines Ticketing - Nuraminah, Ahlijati (LPPM of STIMIK ESQ, 2018)
PT. XYZ is an airline that has developed quite rapidly in Indonesia since 2011. In order to increase ticket sales, PT. XYZ has attempted to implement retail payment system by opening various payment channel which also involves many banks to handle payment. Daily ticket sales transaction data reaches millions every day. Constraints faced by PT. XYZ as well as other major retailers is in the reconciliation / matching phase of data from various payment channel owned and involving many banks that have different data patterns. The wide scope of payments, as well as the possibility of a connection error between the merchant system and the Bank system have made reconciliation more difficult. The reconciliation of payments still needs to be done manually using spreadsheets so it takes more time and process, thus slows down operations. Based on the background, PT. XYZ requires a payment reconciliation system that can handle the data of millions of transactions. This payment reconciliation system is also expected to handle many payment channels and many banks with diverse data patterns. This study aims to analyze and design the payment reconciliation system required by PT. XYZ. The analysis and design process will adapt the Waterfall method for the analysis and design phase. Results from the study concluded that the resulting design is largely able to answer the needs of PT. XYZ to the payment reconciliation system and can be the basis for system implementation at a later stage.